2021
DOI: 10.1089/crispr.2020.0145
|View full text |Cite
|
Sign up to set email alerts
|

Functional Study of the Type II-A CRISPR-Cas System of Streptococcus agalactiae Hypervirulent Strains

Abstract: Nearly all strains of Streptococcus agalactiae, the leading cause of invasive infections in neonates, encode a type II-A clustered regularly interspaced short palindromic repeats (CRISPR)-Cas system. Interestingly, S. agalactiae strains belonging to the hypervirulent Sequence Type 17 (ST17) contain significantly fewer spacers in their CRISPR locus than other lineages, which could be the result of a less functional CRISPR-Cas system. Here, we revealed one large deletion in the ST17 cas promoter region and we ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Most of our CC17/III GBS isolates (95.1%, n = 98) had spacer compositions of 49-53-54-55-56, and we found that 81.6% ( n = 80) of them had spacer acquisition, whereas 11.7% ( n = 12) had spacer loss. Our data support the recent findings of Pastuszka et al that spacer acquisition, sometimes accompanied with the loss of old spacers, occurs and may be more than ~10% of the ST17 clones [ 33 ]. Currently, only very few studies are available regarding the CC17/III GBS lineage [ 34 ], and this phenomenon requires further confirmation after enrolling a larger number of strains.…”
Section: Discussionsupporting
confidence: 92%
“…Most of our CC17/III GBS isolates (95.1%, n = 98) had spacer compositions of 49-53-54-55-56, and we found that 81.6% ( n = 80) of them had spacer acquisition, whereas 11.7% ( n = 12) had spacer loss. Our data support the recent findings of Pastuszka et al that spacer acquisition, sometimes accompanied with the loss of old spacers, occurs and may be more than ~10% of the ST17 clones [ 33 ]. Currently, only very few studies are available regarding the CC17/III GBS lineage [ 34 ], and this phenomenon requires further confirmation after enrolling a larger number of strains.…”
Section: Discussionsupporting
confidence: 92%
“…This indicated that the environment that promoted the evolution of CC12 was complicated and included increased antibiotic pressure. Two CRISPR-Cas systems have been identified in GBS, one belonging to type II-A and the other belonging to type I-C ( Pastuszka et al, 2021 ). In this study, CC10 only had a type II-A CRISPR-Cas system, but CC12 had both type II-A and I-C systems.…”
Section: Discussionmentioning
confidence: 99%
“…Differences have been highlighted according to ST. For example, strains belonging to ST17, considered as hypervirulent because more involved in neonatal infections, have less spacers than other STs (Lier et al, 2015). More recently, specificity in the locus organization has been highlighted for these strains and the system's functionality has been explored (Pastuszka et al, 2021). Thanks to its CRISPR1-Cas system, S. agalactiae can not only defend itself against invaders but also regulate its own genome.…”
Section: Streptococcus Agalactiaementioning
confidence: 99%